Impactos da COVID-19 nas práticas de Experiência dos Pacientes em hospitais brasileiros: uma pesquisa de levantamento com os profissionais de saúde - Bernardo, Juliana Maria Savio (2021)
The concept of customer experience has been widespread in different industrial and service sectors as a positive customer experience in relation to a product, brand and services has the ability to increase levels of satisfaction, loyalty and word-of-mouth communication. In the health area, there is a clear concern with the patient's experience. This is a multidimensional concept focusing on the cognitive, emotional, behavioral, sensory and social responses of patients in relation to direct or indirect interactions with the company providing health services. In the literature on this topic, one of the challenges is how to measure the patient's experience. This assessment becomes more necessary in the context of a pandemic such as that experienced by many countries, including Brazil. Thus, this research aims to measure the impact of the COVID-19 pandemic on patient experience practices in Brazilian hospitals through a closed questionnaire. To achieve this objective, two research methods were adopted. The first refers to a scoping review in the literature on models for measuring the experience of adult patients in general hospitals. The second method refers to conducting a survey type survey by applying a questionnaire on the impact of the COVID-19 pandemic on patient experience practices in Brazilian hospitals. Data were collected for a valid sample of 88 health professionals and / or hospital managers. Among the results of the research, we highlight the identification of the main instruments (HCAHPS, PPE and QPP) and variables (communication and information, work team and care and safety) used to assess the patient's experience. The results also show the relationship of the hospital's response capacity to coping with COVID-19 with the performance of the current and future hospital and with the patient's experience practices and, these, with the performance of the patient's experience. It also shows the positive moderating effect of patient guidance on the hospital's present performance.